2013
DOI: 10.1111/cbdd.12120
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and In Silico Binding of a Cyclic Peptide with Hepatitis B Surface Antigen

Abstract: A specific ligand targeting the immunodominant region of hepatitis B virus is desired in neutralizing the infectivity of the virus. In a previous study, a disulfide constrained cyclic peptide cyclo S(1) ,S(9) Cys-Glu-Thr-Gly-Ala-Lys-Pro-His-Cys (S(1) , S(9) -cyclo-CETGAKPHC) was isolated from a phage displayed cyclic peptide library using an affinity selection method against hepatitis B surface antigen. The cyclic peptide binds tightly to hepatitis B surface antigen with a relative dissociation constant (KD (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Top ten clusters that contained the highest number of trajectories were further analyzed by selecting the trajectories with the following conditions (i) the structure has φ angles within 30°of the φ-values calculated from 3 J (H N -H α ), and (ii) the structure has an interproton distance error <0.5 Å compared to the upper boundaries of distances derived from the NOE restraints. 44 One conformation from each of the top ten clusters that suited the above criteria was then selected to form a structural ensemble and analyzed using the PROCHECK-NMR. 45 The PyMOL (Version 1.3 Schrödinger, LLC) and the Discovery Studio Visualizer 3.5 (Accelrys) were used to view the structural ensembles.…”
Section: Structure Calculationsmentioning
confidence: 99%
“…Top ten clusters that contained the highest number of trajectories were further analyzed by selecting the trajectories with the following conditions (i) the structure has φ angles within 30°of the φ-values calculated from 3 J (H N -H α ), and (ii) the structure has an interproton distance error <0.5 Å compared to the upper boundaries of distances derived from the NOE restraints. 44 One conformation from each of the top ten clusters that suited the above criteria was then selected to form a structural ensemble and analyzed using the PROCHECK-NMR. 45 The PyMOL (Version 1.3 Schrödinger, LLC) and the Discovery Studio Visualizer 3.5 (Accelrys) were used to view the structural ensembles.…”
Section: Structure Calculationsmentioning
confidence: 99%
“…The estimated secondary structure of each peptide‐based inhibitor is shown in Table . The results showed that the peptides consisted of more than 80% random coil structure, which was characterized by the strong negative band at approximately 195 nm . In addition to the predominant random coil structure, there were 10%–16% of α‐helices and a very low percentage (<5%) of β sheets and turns in the structures of the peptides.…”
Section: Resultsmentioning
confidence: 99%